2015
DOI: 10.1037/a0038284
|View full text |Cite
|
Sign up to set email alerts
|

Humans don’t time subsecond intervals like a stopwatch.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. breaks. The decrement in performance we observed far exceeded the stopwatch prediction, and also exceeded the simulated predictions of a modified stopwatch with a slowing pacemaker. The data thus favour either a counter that cannot be paused during sub-second durations or alternative models of sub-second interval duration discrimination which do not posit a count-based metric for time. We disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
(118 reference statements)
1
5
0
Order By: Relevance
“…The question whether subjects time individual intervals or total duration has been addressed before in humans (Hinton and Rao, 2004; Hinton et al, 2004; Laje et al, 2011; Narkiewicz et al, 2015). Buonomano and colleagues used a spatiotemporal task in which subjects had to perform a series of button presses with an elaborated spatial and temporal structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question whether subjects time individual intervals or total duration has been addressed before in humans (Hinton and Rao, 2004; Hinton et al, 2004; Laje et al, 2011; Narkiewicz et al, 2015). Buonomano and colleagues used a spatiotemporal task in which subjects had to perform a series of button presses with an elaborated spatial and temporal structure.…”
Section: Discussionmentioning
confidence: 99%
“…By plotting Std as a function of Go-time, this trend can be observed as a saturating effect at large Go-time s (Figure 3A, right panel). Whether subjects time individual intervals separately, or they time total elapsed time is an important question in timing research (Hinton and Rao, 2004; Hinton et al, 2004; Laje et al, 2011; Narkiewicz et al, 2015). We found that the continuous (Equation 1) and reset (Equation 3) models provided statistically similar fits to our data ( p = 0.13, paired t -test on the Fisher-transformed correlation coefficients between behavioral data and model estimates, t (24) = −1.6; Laje et al, 2011; Figure 3A).…”
Section: Methodsmentioning
confidence: 99%
“…More generally, our current findings favouring sense-specific clocks form part of a wider body of evidence that speaks against single amodal internal stopwatch accounts, like scalar expectancy theory, which can be criticised on both theoretical grounds (e.g. this model achieves scalar timing via an ad hoc multiplicative constant, rather than by any feature of its basic architecture; see Staddon & Higa, 2006) and on empirical considerations (including that humans do not appear able to stop and restart their timer at will, as this model suggests, without suffering large drops in precision; Narkiewicz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to apply a slope analysis method (Ivry & Hazeltine, 1995;Narkiewicz, Lambrechts, Eichelbaum, & Yarrow, 2015) in order to decompose judgment variability into a component contributed by non-scalar operations (including starting and stopping the clock) and a scalar component that grows with the duration being timed (reflecting counter and/or memory processes). With separate estimates, we were able to make predictions regarding the integration of one but not both sources of noise.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate PSE values from the non-linear clock model, the physical duration T 1 that is needed for an interval to be perceived of equal duration as another interval T 2 can be expressed by Where ψ represents the psychometric function that relates physical to perceived duration. The non-linear clock model assumes that: (1) the clock is reset at every filler tone demarcating the beginning of a new subinterval [ 22 ], (2) the complete interval duration is obtained by summing up the perceived durations of the subintervals D , that is , and (3) the relationship between the physical and the perceived duration of the subintervals is logarithmic [ 3 , 7 ] ψ ′( D ) = log( D ).…”
Section: Discussionmentioning
confidence: 99%